Pre-operative Serum Level of Inhibin B as a Predictor of Spermatogenesis Improvement After Varicocelectomy - Dadfar, Mohammad Reza; Ahangarpour, Akram; Habiby, Ali Akbar; Khazaely, Dinyar (Urology Journal, 2010)
Purpose: Due to various reasons, spermatogenesis might not improve after varicocelectomy. Inhibin B, a sertoli cell glycoprotein, has proved itself as a marker of spermatogenesis. In this study, we measured serum level of inhibin B in patients with varicocele and through comparing pre and post operative semen analysis data, we tried to use serum level of inhibin B as a predictor of spermatogenetic improvement. Materials and Methods: This prospective clinical trial was carried out between September 2007 and September 2008 on 36 infertile men with high grade unilateral or bilateral varicocele. Scrotal ultrasonography and measurement of seminal parameters and serum level of inhibin B were performed for the patients and after confirmation of impaired spermatogenesis, they underwent a subinguinal nonmicroscopic varicocelectomy by a single surgeon. Physical examination, scrotal ultrasonography, and semen analysis were repeated at postoperative months of 3 and 6. Statistical data analysis was done by independent and paired sample t test and Spearman’s Rho test. Results: Mean size of the testis remained the same (P = .5), but mean sperm density, normal morphology, and motility all increased statistically significant after the operation (P < .05, P = .042, P = .023). A significant relationship was found between serum levels of inhibin B and the testis sperm count and morphology (P < .05), but not sperm motility (P > 0.05). Conclusion: It seems that serum level of inhibin B can be used as a reliable pre-operative marker of testicular potential activity and can also predict chance of spermatogenesis after varicocelectomy and save patients from useless surgical procedures.